Isolated low levels of high-density lipoprotein cholesterol are associated with an increased risk of coronary heart disease: An individual participant data meta-analysis of 23 studies in the asia-pacific region - Huxley, Rachel; Barzi, F.; Lam, T.; Czernichow, S.; Fang, X.; Welborn, T.; Shaw, J.; Ueshima, H.; Zimmet, P.; Jee, S.; Patel, J.; Caterson, I.; et al. (2011)
Background-: Previous studies have suggested that there is a novel dyslipidemic profile consisting of isolated low high-density lipoprotein cholesterol (HDL-C) level that is associated with increased risk of coronary heart disease, and that this trait may be especially prevalent in Asian populations. Methods and Results-: Individual participant data from 220 060 participants (87% Asian) in 37 studies from the Asia-Pacific region were included. Low HDL-C (HDL <1.03 mmol/L in men and <1.30 mmol/L in women) was seen among 33.1% (95% confidence interval [CI], 32.9-33.3) of Asians versus 27.0% (95% CI, 26.5-27.5) of non-Asians (P<0.001). The prevalence of low HDL-C in the absence of other lipid abnormalities (isolated low HDL-C) was higher in Asians compared with non-Asians: 22.4% (95% CI, 22.2-22.5) versus 14.5% (95% CI, 14.1-14.9), respectively (P<0.001). During 6.8 years of follow-up, there were 574 coronary heart disease and 739 stroke events. There was an inverse relationship between low HDL-C with coronary heart disease in all individuals (hazard ratio, 1.57; 95% CI, 1.31-1.87). In Asians, isolated low levels of HDL-C were as strongly associated with coronary heart disease risk as low levels of HDL-C combined with other lipid abnormalities (hazard ratio, 1.67 [95% CI, 1.27-2.19] versus 1.63 [95% CI, 1.24-2.15], respectively). There was no association between low HDL-C and stroke risk in this population (hazard ratio, 0.95 [95% CI, 0.78 to 1.17] with nonisolated low HDL-C and 0.81 [95% CI, 0.67-1.00] with isolated low HDL-C). Conclusion-: Isolated low HDL-C is a novel lipid phenotype that appears to be more prevalent among Asian populations, in whom it is associated with increased coronary risk. Further investigation into this type of dyslipidemia is warranted. © 2011 American Heart Association, Inc.